Tolle lege. Embodied reading and the "scene of reading". (March 2021) - Benne, Christian
Abstract: This paper explains the theoretical motivation and background for using intellectual and literary historiography as potential sources for the study of reading as an 'embodied' and 'distributed' activity. It illustrates the theory by way of examples from different periods and cultural contexts. It focusses on explaining the concept of the 'scene of reading' and, in particular, the role of gesture in reading and its literary depiction.